Through the Magical Pink Walkway: A Behavior Setting’s Invitation to Embodied Sense-Makers - Harrison, Simon (Frontiers in Psychology, 2020)
This paper examines an intersection between ecological psychology and the enactive approach, brought about by studying sense-making in relation to a behavior setting in Hong Kong and adopting a focus on embodied action and gesture. A cosmetics pop-up store in a downtown shopping mall provides the basis for a case study involving a two pronged analysis. I first use Barker’s behavior setting theory to describe the publically accessible structure and dynamics of the store, which reveals a bounded spatio-temporal structure with several interdependent behavior-milieu parts. I then analyze video recordings of my research participant encountering, entering, and exploring this environment. Following an enactive-informed micro-ethnographic approach to embodied communication, I examine her movements, postures, gestures, and language use as she joins the behavior setting. These fine-grained descriptions of her embodied actions provide an empirical basis to analyze enactive sense-making. On the one hand, they disclose the affective and emotional experience of perceiving relevant affordances in the environment, and on the other hand, they show the specificity of sensorimotor abilities required to join the setting’s standing pattern of behavior.